THE APPLICATION OF REVERSE SHIFT PATTERN TO OPERATOR WORKERS IN THE POWERHOUSE - Deyan Pratama Putra; Mona Lestari; Anita Camelia; Desheila Andarini; Novrikasari; Poppy Fujianti; Titi Nurhaliza (The Indonesian Journal of Public Health, 2023)
Introduction: Companies generally apply a shift system to keep production running. Implementing work shifts is not necessarily independent of the risks, especially for workers who carry it out. Aims: to analyze the impact felt by operator workers from the implementation of the shift work system that is currently being undertaken, in terms of its impact on physiological, performance, psychological, and social aspects. Method: This research used a qualitative approach. The research was conducted at the powerhouse and the informants in this study were management and employees of the powerhouse operator. Collecting the required data was done by interviewing and observation techniques. Meanwhile, the discussion used descriptive method. Result: The results showed that the backward shift pattern applied by the company did not have a break. It is known that there are several impacts felt by workers as a result of implementing backward work shifts, such as disturbed sleep patterns, experiencing digestive disorders such as bloating and diarrhea, feeling excessively depressed, and workers experiencing social interaction barriers outside of work. However, the shift pattern currently applied has no impact on the performance of the operator. Conclusion: The shift pattern implemented has an impact on operator workers, especially on physiological, psychological and social aspects. Therefore, there is still a need for improvement in the shift pattern applied.